(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
The main factor that affects the low production of horticultural crops in Modayag District, East Bolaang Mongondow Regency is pest and disease attacks. Single control, in this case the use of pesticides has not been able to solve the problem of pests and diseases. Therefore, to solve the problem of pests and diseases so that horticultural production can be increased, integrated control technology is carried out. This community service activity was carried out with the aim of improving the ability and capacity of farmers, especially regarding innovation in integrated control technology for horticultural crops. Before the activity was carried out, the PKM team had approached the Tunas Baru farmer group, this had been approved which was marked by a statement letter from the head of the farmer group for counseling on controlling horticultural plant pests. The approach method used for horticultural farmers was to conduct socialization, counseling, discussion and training on integrated pest and disease control and conduct evaluations. The Tunas Baru Farmer Group was very interested and respected the Community Partnership Program activities carried out by the Team from the Faculty of Agriculture, Sam Ratulangi University. At the beginning before the socialization was carried out, all farmers from the Tunas Baru Farmers Group did not yet know well the dangers of unwise use of insecticides on horticultural plants. The application of integrated pest control technology innovations provided a new experience for the Tunas Baru Farmers Group.